Formaldehyde Release From Predispersed Tattoo Inks: Analysis Using the Chromotropic Acid Method. Issue 5 (September 2021) - Liou, Yujie Linda; Voller, Lindsey M.; Liszewski, Walter; Ericson, Marna E.; Siegel, Paul D.; Warshaw, Erin M.
Abstract : Background: Allergic contact dermatitis to tattoo ink may last from weeks to years. Formaldehyde is a strong sensitizer that may be present in predispersed tattoo inks. Objectives: The aim of this study was to evaluate the presence of formaldehyde in predispersed tattoo inks using the chromotropic acid method. Methods: Tattoo inks from 39 companies were evaluated. Inclusion criteria included availability to purchase inks online through US tattoo product wholesalers or individual Web sites. Brands were grouped based on prevalence of use: common, uncommon, or rare. For common brands, 8 colors (primary colors, secondary colors, black, and white) were purchased. For uncommon and rare brands, 5 colors (primary colors, black, and white) were purchased. Each ink was tested with standard chromotropic acid method procedures; concentration of formaldehyde released was quantified using spectrophotometry. Results: In total, 127 tattoo inks were purchased and tested. Ninety-three (73%) tested positive for formaldehyde release; 34 (27%) tested negative. Formaldehyde release did not correlate with color or brand. At least 1 ink from all brands (except 1) was positive for formaldehyde release. Conclusion: Approximately three-quarters of selected US tattoo inks tested positive for formaldehyde release. Clinicians should be aware of tattoo ink as a potential source of formaldehyde.